Uso de Tecnologías de la Informacion y Comunicación y logro de competencias de personal social en estudiantes del quinto ciclo de primaria de la institución educativa pública Miguel Acosta Oyarce, Caballo Cocha 2024 - Elespuru Reategui, Nixon (2025)
This research focused on analyzing the relationship between the use of Information and Communication Technologies (ICTs) and the development of competencies in the Social Personal area in fifth cycle students. The study, of descriptive correlational type and non-experimental design, covered a population of 234 students. Validated surveys and questionnaires were used to collect data, which made it possible to obtain accurate information on the use of ICTs and the development of personal and social competencies. The results of the study revealed a very high positive correlation (rho = 0.942) according to Spearman's correlation, between the use of ICTs and the achievement of Social Personal competencies, suggesting that greater use of ICTs is associated with greater development of social skills. This implies that the effective integration of ICTs in the educational process can have a significant impact on the formation of students who are more competent and prepared to interact in society. These findings support the study's hypothesis and highlight the importance of considering ICTs as a valuable tool for improving education. Furthermore, the results suggest that educational institutions should prioritize the training of teachers in the effective use of ICTs and encourage an integrated approach that combines technology with the development of social skills.